1993
DOI: 10.1346/ccmn.1993.0410303
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of H+ and Cu2+ Adsorption on Calcium-Montmorillonite

Abstract: Abstract--The interaction of H § and Cu2+-ions with Ca-montmorillonite was investigated in 0.1 tool/ dm 3 solutions of Ca(CIO4)z at 298.2 K by potentiometric titrations using both glass electrodes (for H + ) and ion specific electrodes (for Cu z + ). The experimental data were interpreted on the basis of the surface complexation model. The calculations were performed with the least-squares program FITEQL (Westall, 1982) In addition, the ion exchange equilibria Ca 2+ -Cu 2+ and Ca 2+ -H + had to be taken into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 17 publications
(17 reference statements)
9
113
1
1
Order By: Relevance
“…A study of Cu 2+ sorption on montmorillonite (Stadler and Schindler, 1993) suggested that for 3 < pH < 5…”
Section: Resultsmentioning
confidence: 99%
“…A study of Cu 2+ sorption on montmorillonite (Stadler and Schindler, 1993) suggested that for 3 < pH < 5…”
Section: Resultsmentioning
confidence: 99%
“…Generally, a comprehensive description of interfacial reactions should include both ion-exchange and surface complexation (43). As for WC and LPS illites, since the use of background electrolyte (0.1 M NaNO 3 ) effectively controlled the prevailing ionic strength, we only considered the acid-base behavior of the amphoteric surface hydroxyl group 'SOH, and the weakly acidic surface functional group, 'XH, accounting for ion exchange reactions, could be neglected.…”
Section: Illite Suspensionsmentioning
confidence: 99%
“…Ca-montmorillonite was prepared as described in Stadler and Schindler (1993). doo~ spacings of Ca-montmorillonite as well as of other forms of montmorillonite were obtained from X-ray diffraction (Cu ka radiation) and are given in Table 1.…”
Section: Chemicalsmentioning
confidence: 99%
“…Solutions of HCIO4, Ca(C104)2, Ca(OH)z, and Cu(C104) 2 were prepared and analyzed as described in Stadler and Schindler (1993).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation